Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa Di Desa Nyalian Kecamatan Banjarangkan Kabupaten Klungkung - I Wayan Sukayasa; I Putu Fery Karyada; I Made Endra Lesmana Putra (UNHI Press, 2022)
This study focuses on the accountability system which is the most important aspect in managing village fund allocations that function as democratic control in preventing corruption and abuse of authority in the administration of village government. The justification for this study was to conclude the responsibility of town store designation the board in Nyalian Village, Banjarangkan District, Klungkung Regency.Based on the signs of town monetary administration, this study utilizes a subjective distinct examination procedure technique. Data collection techniques used interviews with the village apparatus and BPD as community representatives from each official banjar, documentation and triangulation. The analysis technique used is data decrease, information show and end drawing.The consequences of this review, the Nyalian Village Government has carried out responsibility in dealing with the designation of town assets from the arranging stage to responsibility, but at the accountability stage it has not been fully carried out this is because until January 31, 2022 there has been no delivery to the public through information media as stipulated in the Ministerial Regulation in State of the Republic of Indonesia number 113 of 2014 concerning village financial management